Aphakic Glaucoma after Paediatric Cataract Surgery - Khalid Waheed, Amtul Mussawar Sami, Muhammad Tayyib (Journal of Rawalpindi Medical College, 2014)
Background : To study the development of aphakic glaucoma and other complications after congenital cataract surgery. Methods:In this descriptive study 30 children, from 4 months to 2 years of age, with cataract were enrolled.Patients with ocular trauma, congenital glaucoma, anterior segment dysgenesis, posterior segment abnormalities and retinopathy of prematurity were not included in this study. Anterior and posterior segment examination, retinoscopy, keratometry and ultrasonosgraphy were done to assess retinal status. Pupils were dilated using cyclopentolate1% and phenylepherine10%, at 90, 60, 30 and 15 minutes preoperatively. Surgical procedures included anterior capsulotomy/anterior continuous curvilinear capsulorhexis, irrigation and aspiration of lens matter, posterior capsulotomy or posterior continuous curvilinear capsulorhexis, anterior vitrectomy, 0.1c.c intravitreal dexamethasone injection. All cases remained on topical steroids and cycloplegic eye drops for six weeks. Patients were followed on first postoperative day and first postoperative week for detection of early postoperative complications. Then patients were followed after three months, six months and one year. In every visit patients were evaluated including funduscopy, cycloplegic retinoscopy and record of intraocular pressure. Results: A total 30 eyes of 30 patients were evaluated before surgical intervention. There were 22 male and 8 female patients . Age range was between 4 months to 2 years. Aphakic glaucoma was observed in 7% of patients. Posterior capsular opacification was seen in 64% (Table 1). There were no reported intraoperative complications. After cataract surgery, all eyes were treated with corticosteroids and antibiotic eyedrops for eight weeks. Postoperatively there were no case of corneal decomprensation or endophthalmitis. . The incidence was noticed in patients less than one year of age and cataract surgery was performed under four months of age. Conclusion: Aphakic glaucoma is higher in patients who were operated within twelve months of age for congenital cataracts